Maintaining kidney replacement therapy during armed conflicts - TUĞLULAR, ZÜBEYDE SERHAN (My University, 2024)
The world should be heaving a collective sigh of relief that the COVID-19 pandemic is over, but there has been no respite. A recent consensus statement from the Renal Disaster Relief Task Force of European Renal Association (ERA) highlighted that despite calls from the United Nations for a global ceasefire, in 2020 the number of active conflicts reached a record high since World War II [1]. Hot on the heels of the pandemic came the Russian invasion of Ukraine, the civil war in Sudan, the conflict between Israel and Hamas. Many other conflicts are broiling worldwide, but given less air time [2]. The conflict in Syria is now 12 years old and has become chronic [2]. The war in Yemen has been ongoing for 9 years, the war in Tigray (Ethiopia) continued for 2 years, the war in the Democratic Republic of Congo has persisted for decades, and elsewhere, conflicts of varying magnitudes are ongoing in many countries [2]. By September 2023, over 114 million people had been displaced by conflict and violence worldwide [3].
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; TRANSPLANTASYON; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; TRANSPLANTATION; Transplantasyon; Transplantation